Preventive effect of nucleoprotein on hindlimb unloading-induced capillary regression in rat soleus muscle. (April 2014) - Kanazawa, Y; Maekawa, K; Okumura, Y; Fujita, N; Fujino, H
Abstract We investigated the preventive effects of nucleoprotein on capillary regression and mitochondrial dysfunction induced by unloading in the soleus muscle of rats. Nucleoprotein is a supplement made from soft roe of salmon, and its major components are nucleotides and protamine. Adult male Sprague-Dawley rats were divided randomly into control, hindlimb unloading (HU), and hindlimb unloading plus nucleoprotein administration (HU+ NP) groups. Hindlimb unloading was carried out for 2 weeks in the rats belonging to the HU and the HU+ NP groups. The rats of the HU+ NP group were administered nucleoprotein (500 mg/kg) using a feeding needle twice a day for 2 weeks. Hindlimb unloading resulted in capillary regression, decreased succinate dehydrogenase activity of the muscle fiber, and decreased PGC-1α expression in the soleus muscle. These effects were prevented by administration of nucleoprotein. Nucleoprotein appears to prevent capillary regression and mitochondrial dysfunction caused by unloading of the skeletal muscle. Therefore, nucleoprotein supplementation may be an effective therapy for maintaining capillary network and mitochondrial metabolism of the muscle fiber during an unloading period.